Separation recall: psychophysiological response-patterns in an attachment-related short-term stressor - Ehrenthal, Johannes C.; Friederich, Hans-Christoph; Schauenburg, Henning (Stress and health, 2011)
Attachment theory is a conceptual framework for emotional-motivational behaviour and stress regulation in social relationships. However, few experimental studies have investigated attachment-related autonomic stress responses in adults. In a sample of 50 healthy subjects, we investigated autonomic cardiovascular reactions and subjective stress-load to a newly developed, attachment-related short-term stressor (separation recall, SR). The overall magnitude of the cardiovascular response to SR was comparable to the well established mental arithmetic (MA) stress test. However, the SR induced higher levels of sadness and impaired diastolic blood pressure recovery, whereas MA was associated with higher levels of anger and greater heart rate increase. Recovery scores to the attachment-stressor but not the mental arithmetic were related to attachment avoidance as measured by self-report, especially when taking into account the content of the reported episodes of the SR. In sum, our newly developed attachment-related short-term stressor has proven good performance in a first study.